Courses = Classes: Catch-22 for Small Schools - Charles H. Sederberg (Journal of Research in Rural Education, 1983)
The purpose of this project was to explore an alternative to the grade-level, subject-matter, classroom-group organization for delivery of instructional services in small schools. The method probed the limits of the prevailing classroom organizational model using simulated secondary school master schedules. Equating learning opportunity (courses) with classes offered automatically places small schools at a program disadvantage because they lack the critical mass of students heeded for a comprehensive array of electives. The proposed learning center approach is a multi-grade, multi-course organizational alternative that uncouples the course = class equation through individualized and small group instruction. It is suggested thatby using the learning center approach a school with 180 students in grades 7-12 could offer the same (or better) program as a school with 300 to 374 students using the traditional classroom approach